Causas de mortalidade perinatal em Pelotas, RS (Brasil): utilização de uma classificação simplificada Causes of perinatal mortality in Pelotas, Rio Grande do Sul, Brazil: utilization of a simplified classification - Fernando Celso Barros; Cesar Gomes Victora; J. Patrick Vaughan (Universidade de São Paulo, 1987)
O coeficiente de mortalidade perinatal dos 7.392 nascimentos ocorridos nos hospitais de Pelotas, RS, (Brasil) no ano de 1982, foi de 33,7 por 1.000, e 8,8% dos recém-nascidos pesaram menos de 2.500 g. As causas de mortalidade perinatal foram analisadas utilizando-se a classificação simplifícada proposta por Wigglesworth. Trinta e seis por cento dos óbitos perinatais ocorreram antes do início do trabalho de parto (natimortos antepartum), e destes, 60% pesaram mais de 2.000 g. A segunda causa mais importante de morte foi imaturidade, com 31% dos óbitos. Neste grupo, 21% pesaram mais de 2.000 g. Estes achados, assim como as altas taxas de mortalidade perinatal para grupos específicos de peso ao nascer, sugerem que algumas falhas estão ocorrendo no atendimento de saúde da população materno-infantil em Pelotas, tanto em clínicas de pré-natal como no atendimento do parto. The causes of perinatal mortality among the 7,392 hospital births which occurred in Pelotas, RS, Brazil, during 1982, were analysed using the simplified classification described by Wigglesworth. The main advantage of this classification is that it can be used even in places where post-mortems are seldom performed. The perinatal deaths were classified into five groups: a) macerated fetuses without malformations, b) congenital malformations, c) immaturity, d) asphyxia and e) other causes of death. The perinatal mortality rate was 33.7 per 1,000 births, nearly equally divided between fetal and early neonatal deaths, and 8.8% of the babies were of low birthweight. Thirty-six percent of the perinatal deaths were antepartum stillbirths, and 60% of these weighed 2,000 g. or more. The second most important cause was immaturity, which accounted for 31% of the deaths. In this latter group 21% weighed 2,000 g or more at birth. These findings, as well as the high birthweight-specific perinatal mortality rates, strongly suggest that there are deficiencies in the antenatal and delivery care in Pelotas that need to be promptly corrected. Policies that should be implemented by health planners include: decentralization of antenatal care clinics; utilization in these clinics of the "at-risk concept" to identify women at high risk of delivering low birthweight babies, efforts to increase community participation and home visits in order to attract those pregnant women who do not attend the clinics. In addition, it is mandatory that well trained doctors (obstetricians and paediatricians) should to be available 24 hours a day at the maternity hospitals to assist mothers and babies identified as at high risk.